A Meta‐Regression of 18 Wildfire Chronosequences Reveals Key Environmental Drivers and Knowledge Gaps in the Boreal Nitrogen Balance - Stefan F. Hupperts; Frank Berninger; Han Y. H. Chen; Nicole Fenton; Mélanie Jean; Kajar Köster; Markku Larjavaara; Michelle C. Mack; Marie‐Charlotte Nilsson; Marjo Palviainen; Anatoly Prokushkin; Jukka Pumpanen; et al. (Global Change Biology, 2025)
Climate change has increased the size and frequency of wildfires across the boreal biome. Severe wildfires in boreal forests have been found to trigger shifts from evergreen to deciduous canopies, which has cascading effects on carbon and nitrogen cycling. Ecosystem productivity and carbon uptake in boreal forests are strongly linked with nitrogen, and Earth system models increasingly depend on our understanding of the nitrogen balance to predict post‐fire carbon uptake. To investigate the post‐fire boreal nitrogen balance, we combined a mass balance approach and literature synthesis to estimate rates of nitrogen accumulation and nitrogen inputs across a network of 18 boreal wildfire chronosequences that varied in both wildfire regime and post‐fire canopy type, comprising 527 forest stands. We found that deciduous‐ or mixed‐dominance boreal forests establishing after severe, stand‐replacing fires had the highest nitrogen accumulation rates (15.7 ± 3.8 kg ha −1 year −1 ), while evergreen‐dominated forests establishing after surface‐ or mixed‐severity fires had the lowest nitrogen accumulation rates (1.4 ± 1.1 kg ha −1 year −1 ). Annual known inputs from nitrogen deposition and biological nitrogen fixation combined, estimated from published data, largely failed to explain the rate of nitrogen accumulation, particularly in deciduous or mixed‐dominance forests establishing after stand‐replacing fires, suggesting that the origins of most nitrogen in these forest types remain poorly understood. As the frequency of severe wildfires increases across the boreal biome and shifts toward deciduous canopies become more common, our study reveals a large knowledge gap in the resulting nitrogen balance that needs to be resolved in order to improve predictions of forest carbon uptake.

Disentangling the effect of topography and microtopography on near-ground growing-season frosts at the boreal-temperate forest ecotone (Québec, Canada) - Benjamin Marquis; Yves Bergeron; Martin Simard; Francine Tremblay (New Forests, 2021)

Patterns and determinants of lichen abundance and diversity across a subarctic to arctic latitudinal gradient - Catherine Chagnon; Martin Simard; Stéphane Boudreau (Journal of Biogeography, 2021)
Aim Lichens are a major component of Arctic biodiversity. However, they appear vulnerable to climate change, as they are exposed to warmer temperatures and increased competition with vascular plants. Our study aims to evaluate lichen cover, species richness, functional diversity and community composition among the dominant vegetation types along a 640‐km latitudinal gradient, and to identify environmental determinants related to patterns in lichen communities. Location From subarctic (56°N) to arctic (62°N) Nunavik (Québec, Canada). Taxon Lichens. Methods We characterized macrolichen communities at the species level in 42 sites across a latitudinal gradient, and identified latitudinal trends in lichen cover, species richness and functional diversity. Using linear models and distance‐based redundancy analysis, we investigated the effect of climate, vegetation, topography and soil characteristics on lichen communities. Results Lichen cover and species richness were the lowest at high latitudes, while functional diversity increased with increasing latitude. Vegetation types and surficial deposits were strongly related to lichen cover and richness. However, these factors did not influence functional diversity, which was mainly driven by climatic conditions. Main conclusion Our results highlight the importance of vegetation structure in lichen communities and corroborate the negative relationship between vascular plant abundance and lichen abundance and species richness. While we found no influence of vegetation structure on lichen functional diversity, further studies using targeted functional traits are needed to accurately investigate the impact of ongoing changes in northern vegetation on ecosystem functioning.

Growing‐season frost is a better predictor of tree growth than mean annual temperature in boreal mixedwood forest plantations - Benjamin Marquis; Yves Bergeron; Martin Simard; Francine Tremblay (Global Change Biology, 2020)
Increase in frost damage to trees due to earlier spring dehardening could outweigh the expected increase in forest productivity caused by climate warming. We quantified the impact of growing‐season frosts on the performance of three spruce species (white, black, and Norway spruce) and various seed sources with different frost tolerance in two plantations, established on both sides of the eastern Canadian boreal‐temperate forest ecotone. The objectives of this study were to determine (a) if spruce species and seed sources planted in sites far from their natural provenance would be less adapted to local site conditions, leading to increased frost damage and reduced height growth; (b) at which height above the ground growing‐season frosts ceased to damage apical meristems; and (c) if height growth was best predicted by extreme climatic events (growing‐season frosts) or by mean annual or summer temperature. At each site and for all spruce species and seed sources, we cross‐sectioned spruce trees at different heights above the ground. Tree rings were cross‐dated and screened for frost rings, which were then given a severity score based on cellular damage. Frost severity reduced height growth of all spruce species and provenances at both sites. Height growth of the non‐native Norway spruce was the most reduced by frost severity and was the smallest species at both sites. Frost caused the highest growth reduction in white spruce at the boreal mixedwood site and had the least effect on black spruce at both sites. For all spruce species, height growth was affected up to 2 m above the ground. Model selection based on corrected Akaike's information criteria (AICc) identified that minimum temperature in May was by far the best climate variable predicting tree growth (AICc weight = 1), highlighting the importance of considering extreme climatic events, which are likely to increase in the future.

Assessment of recreational boating as a vector for marine non-indigenous species on the Atlantic coast of Canada - M. Pelletier-Rousseau; R. Bernier; C. Clarke Murray; D. Drolet; A. Lacoursière-Roussel; A. Locke; J. L. Martin; C. H. McKenzie; C. W. McKindsey; T. W. Therriault; N. Simard (Biological Invasions, 2019)

A response to “Personalised medicine and population health: breast and ovarian cancer” - Antonis Antoniou; Hoda Anton-Culver; Alexander Borowsky; Mireille Broeders; Jennifer Brooks; Anna Chiarelli; Jocelyne Chiquette; Jack Cuzick; Suzette Delaloge; Peter Devilee; Michael Dorval; Douglas Easton; et al. (Human Genetics, 2019)

The Interaction Between Insect Outbreaks and Debris Slides in a Glacial Valley of the Eastern Canadian Shield - Martin Simard; Patrick Lajeunesse (Ecosystems, 2015)

miR-20a represses endothelial cell migration by targeting MKK3 and inhibiting p38 MAP kinase activation in response to VEGF - Anne-Laure Pin; François Houle; Maëva Guillonneau; Éric R. Paquet; Martin J. Simard; Jacques Huot (Angiogenesis, 2012)

What explains landscape patterns of tree mortality caused by bark beetle outbreaks in Greater Yellowstone? - Martin Simard; Erinn N. Powell; Kenneth F. Raffa; Monica G. Turner (Global Ecology and Biogeography, 2012)
Aim Bark beetle outbreaks have recently affected extensive areas of western North American forests, and factors explaining landscape patterns of tree mortality are poorly understood. The objective of this study was to determine the relative importance of stand structure, topography, soil characteristics, landscape context (the characteristics of the landscape surrounding the focal stand) and beetle pressure (the abundance of local beetle population eruptions around the focal stand a few years before the outbreak) to explain landscape patterns of tree mortality during outbreaks of three species: the mountain pine beetle, which attacks lodgepole pine and whitebark pine; the spruce beetle, which feeds on Engelmann spruce; and the Douglas‐fir beetle, which attacks Douglas‐fir. A second objective was to identify common variables that explain tree mortality among beetle–tree host pairings during outbreaks. Location Greater Yellowstone ecosystem, Wyoming, USA. Methods We used field surveys to quantify stand structure, soil characteristics and topography at the plot level in susceptible stands of each forest type showing different severities of infestation (0–98% mortality; n = 129 plots). We then used forest cover and beetle infestation maps derived from remote sensing to develop landscape context and beetle pressure metrics at different spatial scales. Plot‐level and landscape‐level variables were used to explain outbreak severity. Results Engelmann spruce and Douglas‐fir mortality were best predicted using landscape‐level variables alone. Lodgepole pine mortality was best predicted by both landscape‐level and plot‐level variables. Whitebark pine mortality was best – although poorly – predicted by plot‐level variables. Models including landscape context and beetle pressure were much better at predicting outbreak severity than models that only included plot‐level measures, except for whitebark pine. Main conclusions Landscape‐level variables, particularly beetle pressure, were the most consistent predictors of subsequent outbreak severity within susceptible stands of all four host species. These results may help forest managers identify vulnerable locations during ongoing outbreaks.

Does Soil Organic Layer Thickness Affect Climate–Growth Relationships in the Black Spruce Boreal Ecosystem? - Igor Drobyshev; Martin Simard; Yves Bergeron; Annika Hofgaard (Ecosystems, 2010)

Pyrethroid tolerance is associated with elevated expression of antioxidants and agricultural practice in Anopheles arabiensis sampled from an area of cotton fields in Northern Cameroon - PIE MÜLLER; MOUHAMADOU CHOUAÏBOU; PATRICIA PIGNATELLI; JOSIANE ETANG; EDWARD D. WALKER; MARTIN J. DONNELLY; FRÉDÉRIC SIMARD; HILARY RANSON (Molecular Ecology, 2008)
Spraying of agricultural crops with insecticides can select for resistance in nontarget insects and this may compromise the use of insecticides for the control of vector‐borne diseases. The tolerance of the malaria vector, Anopheles arabiensis to deltamethrin was determined in a field population from a cotton‐growing region of Northern Cameroon both prior to and midway through the 4‐month period of insecticide application to the cotton crop. A 1.6‐fold increase in the median knockdown time was observed. To determine whether this increased tolerance was associated with constitutively elevated levels of genes commonly associated with insecticide resistance, RNA was extracted from F 1 progeny from family lines of field‐caught mosquitoes and hybridized to the Anopheles gambiae detox chip. The experimental design avoided the confounding effects of colonization, and this study is the first to measure gene expression in the progeny of gravid, wild‐caught mosquitoes. Several genes with antioxidant roles, including superoxide dismutases, a glutathione S‐transferase and a thioredoxin‐dependent peroxidase, and a cytochrome P450 showed elevated expression in mosquito families collected during the insecticide‐spraying programme. These genes may constitute an important general defence mechanism against insecticides. Intriguingly, the levels of expression of these genes were strongly correlated suggesting a common regulatory mechanism.

Fire Severity and Long-term Ecosystem Biomass Dynamics in Coniferous Boreal Forests of Eastern Canada - Nicolas Lecomte; Martin Simard; Nicole Fenton; Yves Bergeron (Ecosystems, 2006)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)